Outreach-focused enterprise network design - Wei, Jikuan (2017)
Since the Internet was invented, the study of the Internet has never stopped, especially in university like Nanyang Technological University. Network learning and design has become a very important course. This project not only helps university students to understand the enterprise network, but also can help Polytechnic and Junior College students to know more about network knowledge through the experiment of simulation the real network environment. In this report, the background and motivation will be introduced firstly. Secondly, it will go into literature review. After the literature review, the report will show what hardware and software tools that going to be used in the project. Then, the report will introduce how the experiments was designed for different groups of audience using different network topology, hardware and software tools. The implementation of all the experiment, process and result tests of experiments also will be shown in detail. At last, the conclusion will summarize the whole project and how to improve this project will be shown in the part of future work.